Satsabhara Night Patrol in Preventing Theft During the Covid-19 Pandemic - Seno Arya Chandra (Advances in Police Science Research Journal, 2021)
The motivated by the levels of motor vehicle theft cases in Rembang District, especially during the Covid-19 Pandemic was confirmed to have spread worldwide since early 2020 . But the performance of night patrol by the Sabhara Unit in prevention of motor vehicle theft is not optimal. This can be proven by the average number of motor vehicle theft claim which is increasing in the last 3 (three) years, mostly in the year of 2020, significantly escalate during the Covid-19 pandemic. The results found that the performance of night patrol in prevetion of motor vehicle theft is highly dependent on the environmental approach, social approach, and criminal justice approach. From the research results, it can be seen that the performance night patrol has not been maximized in management functions such as human resources, budget, facilities, infrastructure, methods, and marketing so that it becomes an inhibiting factor in the conduct of the night patrol in preventing motor vehicle theft. Based on the results of the study, the author advise leaders to carry out analysis and evaluation related to the implementation of night patrol adapted to Covid-19 health protocol, provide opportunity for Sabhara Unit member to join the training of Sabhara functions, prepare the certain budget support needed in night patrol, RIIL fulfilment according to DSP, and maintenance of facilities and infrastructure of the Sabhara Unit.